Reducing MSME Tax Rates and Socialization Against Taxpayer Compliance - Hasbudin; Tuti Dharmawaati; Ruslin (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study was to examine and analyze the effect of reducing MSME tax rates on taxpayer compliance and to examine and analyze the effect of socialization on taxpayer compliance. This type of data uses primary data sourced from a questionnaire sample of 100 taxpayers from a population of 19,877. Data analysis used descriptive analysis and multiple linear regression. The results of the analysis show that the decrease in MSME tax rates has a positive and insignificant effect on taxpayer compliance and tax socialization has a positive and significant effect on taxpayer compliance